Cardiovascular Risk Factors and Masked Hypertension: The Jackson Heart Study. Issue 6 (December 2016) - Bromfield, Samantha G.; Shimbo, Daichi; Booth, John N.; Correa, Adolfo; Ogedegbe, Gbenga; Carson, April P.; Muntner, Paul
Abstract : Masked hypertension is associated with increased risk for cardiovascular disease. Identifying modifiable risk factors for masked hypertension could provide approaches to reduce its prevalence. Life's Simple 7 is a measure of cardiovascular health developed by the American Heart Association that includes body mass index, physical activity, diet, cigarette smoking, blood pressure (BP), cholesterol, and glucose. We examined the association between cardiovascular health and masked daytime hypertension in the Jackson Heart Study, an exclusively African American cohort. Life's Simple 7 factors were assessed during a study visit and categorized as poor, intermediate, or ideal. Ambulatory BP monitoring was performed after the study visit. Using BP measured between 10:00 AM and 8:00 PM on ambulatory BP monitoring, masked daytime hypertension was defined as mean clinic systolic BP/diastolic BP <140/90 mm Hg and mean daytime systolic BP/diastolic BP ≥135/85 mm Hg. Among the 758 participants with systolic BP/diastolic BP <140/90 mm Hg, 30.5% had masked daytime hypertension. The multivariable-adjusted prevalence ratios for masked daytime hypertension comparing participants with 2, 3, and ≥4 versus ⩽1 ideal Life's Simple 7 factors were 0.99 (95% confidence interval [CI], 0.74–1.33), 0.77 (95% CI, 0.57–1.03), and 0.51 (95% CI, 0.33–0.79), respectively. Masked daytime hypertension was less common among participants with ideal versus poor levels of physical activity (ratio, 0.74; 95% CI, 0.56–1.00), ideal or intermediate levels pooled together versus poor diet (prevalence ratio, 0.73; 95% CI, 0.58–0.91), ideal versus poor levels of cigarette smoking (prevalence ratio, 0.61; 95% CI, 0.46–0.82), and ideal versus intermediate levels of clinic BP (prevalence ratio, 0.28, 95% CI, 0.16–0.48). Better cardiovascular health is associated with a lower preva lence of masked hypertension. Abstract : Supplemental Digital Content is available in the text.